EXAMINING THE EFFECTS OF REGULATION, HALAL AWARENESS, AND BELIEF ON MSME INTENTIONS IN MEDAN CITY TO OBTAIN HALAL CERTIFICATION - Lubis, Ilham Akbar Lubis; Sugianto, Sugianto; Imsar, Imsar (Ekonomi Islam, 2025)
Research aims: This study examines how regulation, halal awareness, and belief influence the intention of Micro, Small, and Medium Enterprises (MSMEs) in Medan City to register for halal certification. Although mandated by Law No. 33 of 2014, many MSMEs continue to delay certification due to limited understanding, perceived financial burdens, and assumptions that their products are inherently halal. Design/Methodology/Approach: A quantitative approach using multiple linear regression was applied. Data were collected from 91 MSMEs in East Medan District through a structured questionnaire, supported by validity, reliability, and classical assumption testing. Research findings: The results show that regulation, halal awareness, and belief significantly shape MSME intentions, explaining 90.4% of the variation. Although MSMEs recognize the importance of certification for legality and consumer trust, challenges related to procedures and limited knowledge remain. Theoretical Contribution/Originality: This study enriches the literature by illustrating how regulatory and cognitive–religious factors influence MSME certification decisions. Practical/Policy Implications: Stronger government support, wider socialization, and simpler procedures are needed to increase MSME participation. Research Limitations/Implications: The findings are limited to East Medan District and a quantitative approach; future studies should compare regions or use mixed methods for deeper insights.